Poverty alleviation through youth empowerment programme : a study of Nguru local government in Nigeria - Danladi, Hamza Suleiman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Poverty is a global challenge which almost all countries in the world are currently facing. The problem of poverty is enormous in Nigeria as the evidence shows that the incidence of poverty has risen from about 28.1% in 1980 to 46% in 1986 and continued to rise to 65.6% in 1996 and 70% in 2012 (Fapojuwo et al., 2012). This has led to the realization within the government at all levels in Nigeria that the problem of poverty is a collective responsibility. In view of the above problem, the government at all levels in Nigeria has initiated and implemented different poverty alleviation strategies in order to reduce the incidence of poverty in the country. This study aims at evaluating the youth empowerment programme initiated and implemented by Nguru local government, Yobe State, Nigeria as a strategy for poverty alleviation. The study employed a triangulation technique (quantitative and qualitative methods) in data collection. The population sample of the study is 166 and census study was employed in collecting data from the questionnaire (5-point Likert scale); 116 questionnaires were filled and returned. In addition to the questionnaire, 12 interviews were conducted with five programme beneficiaries, two LG officials, two media workers and three local residents in case the study area. The findings of the study reveal that the youth empowerment programme played a significant and positive role in poverty alleviation to enhance the economic self-reliance of the participants of the programme. It also shows that there is significant relationship between youth empowerment programme, economic self-reliance and poverty alleviation.